Mitochondrial genomes revisited: why do different lineages retain different genes? - Butenko, Anzhelika; Lukeš, Julius; Speijer, Dave; Wideman, Jeremy G (BMC biology, 2024)
The mitochondria contain their own genome derived from an alphaproteobacterial endosymbiont. From thousands of protein-coding genes originally encoded by their ancestor, only between 1 and about 70 are encoded on extant mitochondrial genomes (mitogenomes). Thanks to a dramatically increasing number of sequenced and annotated mitogenomes a coherent picture of why some genes were lost, or relocated to the nucleus, is emerging. In this review, we describe the characteristics of mitochondria-to-nucleus gene transfer and the resulting varied content of mitogenomes across eukaryotes. We introduce a 'burst-upon-drift' model to best explain nuclear-mitochondrial population genetics with flares of transfer due to genetic drift.
Keywords: Evolution, Molecular; Mitochondria; molekulární evoluce; Genome, Mitochondrial; Mitochondrial evolution; fylogeneze; Mitochondrial DNA; CoRR hypothesis; Endosymbiont gene transfer; Mitochondrial mutation rates; sekvence nukleotidů; Base Sequence; mitochondrie; Phylogeny; genom mitochondriální; Evolutionary cell biology; Eukaryota